Kierkegaard: literatura, filosofía, vida - Surghi, Carlos Eugenio (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Three stages can be determined for the becoming of subjects in Søren Kierkegaard’s work: aesthetic, ethical and religious. However, an autobiographical reading makes it possible to identify a fundamental problem in these stages: the figuration of subjectivity in the complex relationship between literature, philosophy and life. The present work seeks to analyze this relationship through two biographical facts, the death of the father and the breaking off of his engagement, as experiences that allow Kierkegaard to elaborate a fundamental concept: conception of life, which not only accounts for what in general terms is called a philosophy of existence, but also allows us to read a narrative of the Self where writing becomes a singular enunciation due to the combined presence of thought and experience.